Static electromagnetic frequency changers - Rozhanskiĭ, Lev Lazarevich (International series of monographs on electronics and instrumentation, 1963)
Static Electromagnetic Frequency Changers is about the theory, design, construction, and applications of static electromagnetic frequency changers, devices that used for multiplication or division of alternating current frequency. It is originally published in the Russian language. This book is organized into five chapters. The first three chapters introduce the readers to the principles of operation, the construction, and the potential applications of static electromagnetic frequency changers and to the principles of their design. The two concluding chapters use some hitherto unpublished work.